An unusual case of neural palatal swelling - Poonja, Preethi A.; Sattur, Atul P.; Burde, Krishna N.; Hallikeri, Kaveri; Anehosur, Venkatesh S. (International Journal of Health Sciences, 2017)
Neural tumors in the oral cavity occur both in the soft tissues and in the jaw bones. They occur as painless, smooth surface swelling in the soft tissues of the mouth, exhibiting a slow rate of growth and mild expansion of the cortical plates. Here, we report a rare case of a cellular variant of schwannoma in a young Indian female patient who presented with an asymptomatic nodule in the mid-palatine raphe region of the hard palate, mimicking a fibroma, thus creating a dilemma in the diagnosis.